Composite skin substitutes, 3D skin bioprinting and the “BioMask” concept in regenerating skin defects - review - Kiełt, Weronika; Kozłowska, Julia; Broniec, Gabriela; Wajdowicz, Barbara; Kudła, Aleksandra; Czapiewska, Rozalia; Dziewulska, Aleksandra; Wróbel, Aleksandra; Pacek, Laura; Kowalska, Klaudia (Journal of Education, Health and Sport, 2024)
The treatment of skin trauma, especially facial skin trauma, is a major challenge due to its complex structure, the presence of appendages, color, texture, and the large area to be reconstructed in extensive trauma. “The gold standard” for treating trauma is autologous intermediate thickness skin grafting. An alternative solution is the usage of bioengineered skin substitutes. Tissue engineering is intended to provide patients with better treatment options and more effective pain reduction. Unique skin lesions are those related to the face. To fulfill the need to improve the results of facial skin reconstruction, the “Biomask” concept was introduced for the treatment of facial wounds. The purpose of this review is to analyze composite dermal-epidermal substitutes already on the market for clinical use, as well as briefly discussing materials in the testing phase, focusing on 3D skin bioprinting and facial trauma regeneration using “BioMask”. PubMed and Google Scholar databases were searched for relevant sources. Search terms included “skin substitutes”, “synthetic skin substitutes”, “bioengineered skin”, “composite skin substitutes” and additionally each analyzed unit of composite skin substitutes was searched. Bioengineered skin substitutes effectively fulfill the role of dressings during the reconstruction of skin injuries. The development of 3D skin bioprinting is enabling the increasing and effective use of these materials. The high requirements in the treatment of facial skin injuries are the trigger for the development of new materials such as "BioMask". The synergy of new technologies makes it possible to create improved methods of wound dressing and reconstruction of skin defects.